Vesicle-micelle transition in aqueous mixtures of the cationic dioctadecyldimethylammonium and octadecyltrimethylammonium bromide surfactants - Alves, Fernanda Rosa; Zaniquelli, Maria Elisabete D.; Loh, Watson; Castanheira, Elisabete M. S.; Oliveira, M. Elisabete C. D. Real; Feitosa, Eloi (Elsevier B.V., 2007)
The vesicle-micelle transition in aqueous mixtures of dioctadecyidimethylammonium and octadecyltrimethylammonium bromide (DODAB and C(18)TAB) cationic surfactants, having respectively double and single chain, was investigated by differential scanning calorimetry (DSQ, steady-state fluorescence, dynamic light scattering (DLS) and surface tension. The experiments performed at constant total surfactant concentration, up to 1.0 mM, reveal that these homologous surfactants mix together to form mixed vesicles and/or micelles, depending on the relative amount of the surfactants. The melting temperature T-m of the mixed DODAB-C(18)TAB vesicles is larger than that for the neat DODAB in water owing to the incorporation of C(18)TAB in the vesicle bilayer. The surface tension decreases sigmoidally with C(18)TAB concentration and the inflection point lies around (XDODAB) approximate to 0.4, indicating the onset of micelle formation owing to saturation of DODAB vesicles by C(18)TAB molecules. When XDODAB > 0.5 C(18)TAB molecules are mainly solubilised by the vesicles, but when XDODAB < 0.25 micelles are dominant. Fluorescence data of the Nile Red probe incorporated in the system at different surfactant molar fractions indicate the formation of micelle and vesicle structures. These structures have apparent hydrodynamic radius RH of about 180 and 500-800 nm, respectively, as obtained by DLS measurements. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: DODAB; C(18)TAB; surfactant; DSC; tensiometry; light scattering; melting temperature; nile red; steady-state fluorescence